Organic petrology and Rock-Eval characteristics in selected surficial samples of the Tertiary Formation, South Sumatra Basin - Hermiyanto, M. H.; Ningrum, N. Sudini (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20096Organic petrologic data of the DOM of Talangakar and Muaraenim Formations show that the organic matter consisting mainly of vitrinite group is essentially composed of telocollinite (1.0 â 70.8 %) and desmocollinite (0.8 â 66.6 %) with minor telinite (0.6 â 9.4 %), detrovitrinite (0.6 â 6.0 %), and cor- pocollinite (0.6 â 2.0 %). Minor exinite (0.4 â 7.8 %) and inertinite (0.4 â 8.0 %) are also determined. However, mineral matter varies from 0.6 â 99.44 %. Downwards, the increase in vitrinite reflectance (0.33 â 0.48 %) is concomitant with the depth of each formation. Furthermore, based on Rock-eval pyrolysis, TOC value of the Talangakar Formation ranges from 0.09 â 15.38 %, Gumai 0.34 â 0.39 %, Airbenakat 0.32 â 4.82 %, and Muaraenim between 0.08 â 15.22 %. Moreover the PY (Potential Yield) value variation of the Talangakar, Gumai, Airbenakat, and Muaraenim Formations are between 0.04 â 36.61 mg HC/g rock, 0.53 â 0.81 mg HC/g rock, 0.1 â 4.37 mg HC/g rock, and 0.07 â 129.8 mg HC/g rock respectively. Therefore, on the basis of those two parameters, the four formations are included into a gas - oil prone source rock potential. However, the Talangakar and Muaraenim Formations are poor to excellent category, whereas the Air Benakat tends to indicate a poor â fair category and Gumai Formation are only within a poor category. Tmax value of the Talangakar ranges from 237 â 4380 C, Gumai 316 â 3590 C, Airbenakat 398 â 4340 C with exceptions of 4970 C and 5180 C, and Muaraenim Forma- tions 264 â 4250 C. The Talangakar Formation contains kerogen Type II dan III, with the HI (Hydrogen Index) value varies from 45.16 â 365.43. However two samples show value of 0. The organic content of the Gumai and Air Benakat Formations are included into kerogen type III, with HI value ranges from11.87 â 40.82, and 19 â 114 respectively. Moreover the Muaraenim Formation has two category of kerogen type and HI value, those are type III with the HI value of 1 and kerogen type I with HI value of 821.29. The diagram of Tmax vs HI shows that the organic thermal maturation of the four formations are included into an immature to mature level.Â Â